Tapung Hilir Police Strategy in Investigating Narcotics Crimes (Case Study at Tapung Hilir Police), - Kurnia, Errik; Syahrul Akmal Latif, (Sisi Lain Realita, 2023)
Tapung Hilir Police Strategy in Investigating Narcotics Crimes (Case Study at Tapung Hilir Police), Based on the background description above, the formulation of the problem in this research is What is the strategy used by the Tapung Hilir Police in Investigating Narcotics Trafficking Cases. The aim of this research is: To find out the strategies used by the Tapung Hilir Police in investigating narcotics trafficking cases. In this research, the author uses a qualitative research approach, namely descriptive research. The most practical way to do this is to conduct in-depth interviews. The type of research used by the author is descriptive research which describes the actual situation. In an effort to deal with narcotics cases, the Tapung Hilir Police implemented several strategies to prevent narcotics crimes by carrying out coaching (pre-emptive), prevention (preventive) and enforcement (repressive) efforts. The Police in applying criminal sanctions to perpetrators of narcotics crimes based on the provisions of Law Number 35 of 2019 concerning Narcotics with the criminal provisions contained in Articles 111 to Article 147, taking into account the principles of criminal law where there are at least 2 pieces of evidence which is valid in accordance with article 183 of the Criminal Procedure Code and prioritizes the principle of inclusion (deelneming) in the Criminal Code.